Measuring the efficiency of banks using a two-stage DEA model - Martins,Ana Isabel (2009)
Facing the biggest world-wide crisis of the last 30 years, significant losses in revenues are foreseen for the banking sector as well as an increasing competitive pressure. Using data from 2007, this study evaluates the efficiency of the 37 major banks operating in Portugal through DEA methodology. Efficiency is evaluated trough Chen and Zhu (2004) two-stage model applied to the banking industry, circumventing the usual problem inherent in the existence of two approaches (Production/Intermediation). The main contribution of this study is the incorporation of new variables that reflect, besides profitability, value creation and risk, such as intrinsic value added. It is usual to apply standard DEA models to each stage to typically two-stage processes. However, such an approach may conclude that two inefficient stages lead to an overall efficient DMU with the inputs of the first stage and outputs of the second stage. The distortion/improvement in the DEA frontier is caused by the presence of intermediate measures. Efficiency is analyzed under a global perspective including all banks, assuming that all access the same technology. Subsequent analysis is made to the efficiency by groups based on size/business and risk factors, estimated separate frontiers, analyzed the inefficiencies intra-groups and differences among groups.